2022
DOI: 10.1093/mnrasl/slac078
|View full text |Cite
|
Sign up to set email alerts
|

Can we reveal the core-chemical composition of ultra-massive white dwarfs through their magnetic fields?

Abstract: Ultra-massive white dwarfs ($1.05 \rm M_\odot \lesssim M_{WD}$) are particularly interesting objects that allow us to study extreme astrophysical phenomena such as type Ia supernovae explosions and merger events. Traditionally, ultra-massive white dwarfs are thought to harbour oxygen-neon (ONe) cores. However, recent theoretical studies and new observations suggest that some ultra-massive white dwarfs could harbour carbon-oxygen (CO) cores. Although several studies have attempted to elucidate the core composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…These groups cite Isern et al (2017) and/or Ginzburg et al (2022) as a possible explanation for this. In a novel use of the findings of Isern et al (2017), Camisassa et al (2022) infer the existence of O/Ne cores based on the existence of magnetic fields in white dwarfs that are too hot to be crystallizing if they have C/O cores but are expected to be crystallizing if they are O/Ne.…”
Section: Magnetic Field Generationmentioning
confidence: 99%
“…These groups cite Isern et al (2017) and/or Ginzburg et al (2022) as a possible explanation for this. In a novel use of the findings of Isern et al (2017), Camisassa et al (2022) infer the existence of O/Ne cores based on the existence of magnetic fields in white dwarfs that are too hot to be crystallizing if they have C/O cores but are expected to be crystallizing if they are O/Ne.…”
Section: Magnetic Field Generationmentioning
confidence: 99%
“…Among these studies, the most promising solutions invoke 22 Ne distillation (Blouin et al 2021) and 22 Ne sedimentation processes (Camisassa et al 2021) occurring in ultramassive white dwarfs with CO cores. All attempts to reproduce the necessary cooling delay in ultramassive white dwarfs with ONe cores have failed, and this is particularly interesting because, to date, there is no clear evidence that ultramassive white dwarfs harbor CO or ONe cores (see e.g., Camisassa et al 2022b, for a thorough discussion).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in compositionally driven convection in white dwarfs has also been recently revived with the suggestion of Isern et al (2017) that it leads to a magnetic dynamo in crystallizing white dwarfs (Schreiber et al 2021a(Schreiber et al , 2021b(Schreiber et al , 2022Belloni et al 2021;Camisassa et al 2022;Ginzburg et al 2022). Using the scaling of Christensen et al (2009) for a saturated dynamo, Isern et al (2017) found that fields up to ∼1 MG could be generated.…”
Section: Introductionmentioning
confidence: 99%